2021
DOI: 10.14710/ijred.2021.33942
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hot Equal Channel Angular Processing (ECAP) Consolidation Technique in the Production of Boron Carbide(B4C)-Reinforced Aluminium Chip (AA6061)-Based Composite

Abstract: The production of metal matrix composites (MMCs) through recycled materials is a cost-saving process. However, the improvement of the mechanical and physical properties is another challenge to be concerned. In this study, recycled aluminium 6061 (AA6061) chips reinforced with different volumetric fractions of boron carbide (B4C) were produced through hot equal channel angular processing (ECAP). Response surface methodology (RSM) was carried out to investigate the dependent response (compressive strength) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Table 3 demonstrates the experimental design and predicted model UTS strength, RSM findings of tensile strength responses were generated after multiple number of experiments which investigated the parameters of preheating temperature, ZrO 2 and B 4 C volume fraction proportions. The presented pareto chart determines the factors magnitude which are crossing the line reference where, the reference lines confirm that the investigated parameters are significant absolute values cause interactions between parameter towards to the UTS materials strength [ 2 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Table 3 demonstrates the experimental design and predicted model UTS strength, RSM findings of tensile strength responses were generated after multiple number of experiments which investigated the parameters of preheating temperature, ZrO 2 and B 4 C volume fraction proportions. The presented pareto chart determines the factors magnitude which are crossing the line reference where, the reference lines confirm that the investigated parameters are significant absolute values cause interactions between parameter towards to the UTS materials strength [ 2 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 90%
“…Due to economic constraints, production difficulties and materials modification limitations, process enhancement is necessary to achieve further improvement in cost savings, efficiency enhancement, and hybrid material properties. Over the past two decades, composites made from recycled Al-alloys have taken the lead in light metal processing techniques, specifically through solid-state recycling (direct recycling) [ 1 , 2 ] (see Fig. 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using continuous dynamic recrystallization, they achieved ultra-fine grain structure. Alimi et al [253] recycled AA6061chips reinforced with different volumetric fractions of boron carbide using ECAP. The results indicated that boron carbide and the number of passes have a significant effect on the recycled AA 6061 chips.…”
Section: Equal Channel Angular Pressing (Ecap)mentioning
confidence: 99%
“…The highest reported values of compressive strength were samples one and five. The material properties were strengthened by producing dislocations that pile up the total work hardening of the processed deformed specimens [38]. Therefore, the compression strength differed depending on the percentage values of reinforced particles mixed to aluminium AA6061 chips during the forming process.…”
Section: Compressive Strengthmentioning
confidence: 99%